1999
DOI: 10.1080/10273660008833042
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Modelling of Tumour Invasion and Metastasis

Abstract: In this paper we present two types of mathematical model which describe the invasion of host tissue by tumour cells. In the models, we focus on three key variables implicated in the invasion process, namely, tumour cells, host tissue (extracellular matrix) and matrix-degradative enzymes associated with the tumour cells. The first model focusses on the macro-scale structure (cell population level) and considers the tumour as a single mass. The mathematical model consists of a system of partial differential equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
404
2
5

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 321 publications
(427 citation statements)
references
References 43 publications
12
404
2
5
Order By: Relevance
“…The cell species velocity is obtained from a Darcy's law coarse scale reformulation of the inertialess momentum equation, which is the instantaneous equilibrium among the following forces: pressure, resistance to motion (cell-adhesion), elastic forces, forces exchanged with the ECM leading to haptotaxis and chemotaxis and other mechanical effects (e.g. [59,212,55,74,181,127,11,10,12,51,3,25,48,79,16,133,90,39,40,5,135,6,43,50]. Cells produce proteases, which degrade the matrix locally, making room for cells to migrate.…”
Section: Methods Descriptionmentioning
confidence: 99%
“…The cell species velocity is obtained from a Darcy's law coarse scale reformulation of the inertialess momentum equation, which is the instantaneous equilibrium among the following forces: pressure, resistance to motion (cell-adhesion), elastic forces, forces exchanged with the ECM leading to haptotaxis and chemotaxis and other mechanical effects (e.g. [59,212,55,74,181,127,11,10,12,51,3,25,48,79,16,133,90,39,40,5,135,6,43,50]. Cells produce proteases, which degrade the matrix locally, making room for cells to migrate.…”
Section: Methods Descriptionmentioning
confidence: 99%
“…Here L 0 is a length scale, defined as the maximum invasion distance of the cancer cells at the "normal" of invasion (Anderson et al, 2000). Usually L 0 is in the range of 0.1-1cm.…”
Section: Non-dimensionalisation Of the Modelmentioning
confidence: 99%
“…Following the approach of Anderson et al (2000); Gerisch & Chaplain (2008), we choose to ignore the ECM remodelling terms for this model, i.e. we always use γ = 0.…”
Section: Derivation Of the Modelmentioning
confidence: 99%
“…The two-and three-dimensional capillary networks generated by these models compare very favourably with those observed in in vivo experiments (Anderson and Chaplain, 1998). This latter approach can also be used to address metastasis and it has been shown that whereas a continuum model will predict a spreading mass, the probabilistic-type model does show single cells breaking away from the central mass, reminiscent of observations on mammograms showing breast cancer (Anderson et al, 2000).…”
Section: Previous Mathematical Modelsmentioning
confidence: 48%
“…However, in vivo, tissues have a high degree of fine-scaled spatial structure and the paper by Anderson et al (2000) investigates the effects of spatial heterogeneity. Mathematical models of cancer chemotherapy have also been developed to investigate, for example, the use of targeted antibody-enzyme conjugates for the selective activation of anti-cancer prodrugs (Jackson et al, 2000) and the effects of drug resistance on the optimal scheduling of drugs (Murray, 1997).…”
Section: Previous Mathematical Modelsmentioning
confidence: 99%